Measuring lecturer's perception in STEM approach based contextual learning implementation - Haerul Pathoni; Rayandra Asyhar; Maison Maison; Nizlel Huda (OmniaScience, 2022)
21st century education marked with advances in information and communication technology increasing rapidly. Integrated learning in science, technology, engineering and mathematical (STEM) was one of the 21st century learning trends. A non-test instrument has been developed that used to measure lecturers' perceptions in the STEM approach. Based on the results of the analysis and data processing, the non-test instruments were reliable and valid. The test results obtained cronbach's alpha were 0.750 for the material, 0.896 for the construct and 0.778 for the language. This Cronbach Alpha number included in the high reliability category with a cronbach alpha number > 0.05. Meanwhile, the average validity value of the expert approval level for the instrument increased from 81.5% in the good category to 93% with the very good category. While the coefficients cohen's kappa value were 0.038; 0.033; and -0.019. It means that there were low agreement between each of the experts being compared. The results of the lecturers' perceptions about the STEM approach in learning were mostly very good. However, the willingness of the lecturers greatly influences the implementation of STEM in their learning.